QUANTUM FOG CLOUD MODEL IN INTERNET OF THINGS WITH ANALYSIS OF GREEN COMPUTING - Gupta, Sayantan (International Journal of Research -GRANTHAALAYAH, 2017)
The technology of Quantum Green Computing has been discussed in this paper. It also discusses the need of the many implementation techniques and approaches in relation with Fog-Cloud Computing. Moreover, we would like to introduce the latest algorithms like Stack Algorithm, Address Algorithm and many others which will help in the analysis of Green-Quantum Computing Technology in the modern society and would create a technological revolution. With the Internet of Things rising in the modern world time, new security issues have also been developed. So, our proposed Model the Fog-Things Model will help us to determine the security issues and indeed secure the entire IoT network.